Two Novel AGXT Mutations Cause the Infantile Form of Primary Hyperoxaluria Type I in a Chinese Family: Research on Missed Mutation - Lu, Xiulan; Chen, Weijian; Li, Liping; Zhu, Xinyuan; Huang, Caizhi; Liu, Saijun; Yang, Yongjia; Zhao, Yaowang (Frontiers in Pharmacology, 2019)
Primary hyperoxaluria type 1 (PH1) is a rare metabolic disorder characterized by a defect in the liver-specific peroxisomal enzyme alanine-glyoxylate and serine-pyruvate aminotransferase (AGT). This disorder results in hyperoxaluria, recurrent urolithiasis, and nephrocalcinosis. Three forms of PH1 have been reported. Data on the infantile form of PH1 are currently limited in literature. Despite the fact that China is the most populated country in the world, only few AGXT mutations have been reported in several Chinese PH1 patients. In the present study, we investigated a Chinese family in which two siblings are affected by the infantile form of PH1. Sanger sequencing was carried out on the proband, but the results were misleading. Two novel missense mutations (c.517T>C/p.Cys173Arg and c.667A>C/p.Ser223Arg) of the AGXT gene were successfully detected through whole-exome sequencing. These two mutations occurred in the highly conserved residues of the AGT. Four software programs predicted both mutations as the cause of the disease. Postmortem examination was performed and revealed the occurrence of global nephrocalcinosis on both kidneys. The crystals were collected and analyzed as calcium oxalate monohydrate. This study extends the knowledge on the clinical phenotype–genotype correlation of the AGXT mutation. That is, (i) two novel missense mutations were identified for the infantile form of PH1 and (ii) the same AGXT genotype caused the same infantile form of PH1 within the family.